THE RELEVANCE AND IMPORTANCE OF FATWAS IN MUSLIM SOCIETIES - Khaydarov Mirodil Mirvaxidovich (Web of Journals Publishing, 2025)
Fatwas, or Islamic legal opinions issued by qualified scholars, play a pivotal role in contemporary Muslim societies, serving as a bridge between traditional Islamic jurisprudence and modern societal challenges. This paper explores the relevance and importance of fatwas in addressing complex ethical, social, and legal issues faced by Muslim communities in an era of rapid globalization. Fatwas provide authoritative guidance on matters ranging from personal conduct to public policy, reflecting the dynamic interplay between religious principles and evolving societal norms. The study examines the historical evolution of fatwas, their role in addressing contemporary issues such as gender rights, public health, and financial ethics, and their influence on political and social dynamics within Muslim societies. The paper highlights the adaptability of fatwas in responding to modern challenges, such as the COVID-19 pandemic, where fatwas issued by institutions like the Indonesian Ulema Council (MUI) helped reconcile religious obligations with public health guidelines. It also discusses the role of fatwas in promoting social justice, gender equality, and minority rights, emphasizing the progressive interpretations of scholars like Yūsuf al-Qarāḍāwī. Furthermore, the study explores the process of issuing fatwas, the distinction between fatwas and formal legal rulings, and the impact of fatwas on public health, family law, and political governance. The research underscores the importance of responsible fatwa issuance, particularly in avoiding extremist interpretations that can distort Islamic teachings and create societal divisions. It also examines the role of digital platforms in disseminating fatwas, enabling scholars to address contemporary issues more effectively. The paper concludes by emphasizing the need for interdisciplinary approaches to Islamic legal studies, integrating insights from sociology, ethics, and international law to ensure the continued relevance of fatwas in a globalized world. Ultimately, fatwas serve as essential tools for guiding Muslim societies through the complexities of modernity while preserving the core tenets of Islamic jurisprudence.
Keywords: Fatwas, Islamic Jurisprudence (Fiqh), Globalization, Social Justice, Gender Equality, Public Health, Political Governance, Ethical Dilemmas, Responsible Fatwa Issuance, Digital Platforms, Progressive Interpretations,Minority Rights, COVID-19 Pandemic, Islamic Legal Rulings, Interdisciplinary Approaches.